Human umbilical cord mesenchymal stem cell exosome-derived miR-874-3p targeting RIPK1/PGAM5 attenuates kidney tubular epithelial cell damage - Yihang Yu; Meiling Chen; Qitong Guo; Lianju Shen; Xing Liu; Jianbo Pan; Yuanyuan Zhang; Tao Xu; Deying Zhang; Guanghui Wei (Cellular & Molecular Biology Letters, 2023)
Abstract Background Kidney insults due to various pathogenic factors, such as trauma, infection, and inflammation, can cause tubular epithelial cell injury and death, leading to acute kidney injury and the transformation of acute kidney injury to chronic kidney disease. There is no definitive treatment available. In previous studies, human umbilical cord mesenchymal stem cells have been shown to promote kidney injury. In this preclinical study, we investigate the role and mechanism of human umbilical cord mesenchymal stem cell exosomes (HucMSC-Exos) on the repair of renal tubular epithelial cells after injury. Methods C57BL/6 mice underwent unilateral ureteral obstruction, and epithelial cell injury was induced in HK-2 cells by cisplatin. HucMSC-Exos were assessed in vivo and in vitro. The extent of renal cell injury, activation of necroptosis pathway, and mitochondrial quality-control-related factors were determined in different groups. We also analyzed the possible regulatory effector molecules in HucMSC-Exos by transcriptomics. Results HucMSC-Exo inhibited necroptosis after renal tubular epithelial cell injury and promoted the dephosphorylation of the S637 site of the Drp1 gene by reducing the expression of PGAM5. This subsequently inhibited mitochondrial fission and maintained mitochondrial functional homeostasis, mitigating renal injury and promoting repair. In addition, HucMSC-Exo displayed a regulatory role by targeting RIPK1 through miR-874-3p. Conclusion The collective findings of the present study demonstrate that HucMSC-Exos can regulate necroptosis through miR-874-3p to attenuate renal tubular epithelial cell injury and enhance repair, providing new therapeutic modalities and ideas for the treatment of AKI and the process of AKI to CKD transformation to mitigate renal damage.